1997
DOI: 10.1183/09031936.97.10092055
|View full text |Cite
|
Sign up to set email alerts
|

Arterial endothelin-1 level in pulmonary emphysema and interstitial lung disease. Relation with pulmonary hypertension during exercise

Abstract: Arterial endothelin-1 level in pulmonary emphysema and interstitial lung disease. Relation with pulmonary hypertension during exercise. T. Yamakami, O. Taguchi, E.C. Gabazza, M. Yoshida, T. Kobayashi, H. Kobayashi, H. Yasui, H. Ibata, Y Adachi. ERS Journals Ltd 1997. ABSTRACT: This study was undertaken to assess the arterial plasma levels of endothelin-1 (ET-1) and their relationship with pulmonary haemodynamic and gas exchange variables during exercise in patients with emphysema and interstitial lung disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 39 publications
2
23
1
Order By: Relevance
“…In agreement with previous studies, we found that the nondesaturator COPD patients had higher levels of PaO 2 and lower levels of ET-1 than the desaturators when awake [55, 57, 58]. Tatsuo et al [59]found that plasma ET-1 levels were not affected by acute progression of hypoxia and pulmonary hypertension in COPD patients during exercise.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with previous studies, we found that the nondesaturator COPD patients had higher levels of PaO 2 and lower levels of ET-1 than the desaturators when awake [55, 57, 58]. Tatsuo et al [59]found that plasma ET-1 levels were not affected by acute progression of hypoxia and pulmonary hypertension in COPD patients during exercise.…”
Section: Discussionsupporting
confidence: 80%
“…This vasoconstricting peptide may play a relevant role in the pathogenesis of pulmonary hypertension [47, 48, 49]. Increased pulmonary and peripheral blood levels of ET-1 have been described in primary pulmonary hypertension, bronchial asthma, acute lung injury, fibrosing alveolitis, interstitial lung disease and emphysema [50, 51, 52, 53, 54, 55, 56]. Yamakami et al [55]performed cycle ergometry and found that ET-1 levels were statistically significantly correlated with arterial oxygen fall in interstitial lung disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the circulating levels of ET-1 increased in patients with emphysema, and endothelins act as proinflammatory agents (Yamakami et al, 1997). In vitro, ET-1 has been shown to stimulate the release of the cytokines TNF-α, IL-1β, IL-6, and IL-8 (Helset et al, 1993;Huribal et al, 1994), and a study showed that ET-1 antagonism strongly inhibited the production of these cytokines within the airways (Finsnes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…2) Formation of alveolar fibrin clots due to impaired intra-alveolar fibrinolysis providing a lead structure for fibroblast chemotactic migration and proliferation as well as for neovascularisation [29,30,43]. 3) Growth factors such as TGF-b, insulin-like growth factor-1, platelet-derived growth factor (PDGF) and CTGF play a crucial role in the expansion of connective tissue and vascular remodelling in the lungs [44][45][46][47][48][49][50][51]. 4) Epithelial cell apoptosis and impaired epithelial regeneration and epithelial-to-mesenchymal transdifferentiation linked to integrin signalling promotes fibrotic tissue remodelling [52,53].…”
Section: Basic Aspects Of Pulmonary Fibrosis and Phmentioning
confidence: 99%